RISIKO MENINGGAL KELOMPOK CONFIRM COVID-19, PDP, DAN ODP DI JAWA TIMUR - Fibia Sentauri Cahyaningrum; Nola Riwibowo; Isna Ayu Saftri K D; Abdun Nafi Kurniawan; Taruna Firlian Tama (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
Coronavirus Disease 2019 (COVID-19) is a disease caused by a new type of virus called Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Based on data up to April 9th 2020, confirmed cases of COVID-19 in East Java are 6.78% of the total confirmed cases in Indonesia. Meanwhile, cases of death due to COVID-19 are 6.07% of the total cases of death in Indonesia. In handling it, the Ministry of Health of the Republic of Indonesia classifies COVID-19 patients into 3 status levels, namely ODP, PDP and Confirmed. The results of the meta-analysis using the risk ratio with the Mantel-Haenszel fixed effect model obtained a pooled risk ratio for the PDP and ODP groups (RR = 33.66, 95% CI: 20.88-54.27), the confirmed and ODP groups (RR = 56.31, 95% CI: 32.07-98.87), and the confirmed and PDP groups (RR = 1.75, 95% CI: 1.2-2.53). The order of the group with the highest risk of death is Confirmed > PDP > ODP.